SLANG LANGUAGE IN JESSIE J’S SONG LYRICS - Halawa, Hanna Putri; Sitorus, Lola Theresia; Silitonga, Andi Jaihutan; Siahaan, Hiace Vega Fernando (LPPM Universitas Darma Agung, 2023)
This thesis deals with Slang Words in Jessie J’s Song Lyrics. This study aims at finding out the slang words in Jessie J’s Song Lyrics; the most dominant type of slang words in Jessie J’s Song Lyrics; and the reason of the dominant type word in Jessie J’s Song Lyrics. This study applies qualitative and quantitative research method. Based on the types, It was found that there are 22 slang words in ten Jessie J’s Song Lyrics; Shortened Sentence Forms (til,shh, I’mma, cause, ain’t).Society Slang (Damn, Fuck up, Bitch, L.A, FB), Blending (Gotta, Woulda, Gonna, Wanna), and Someone’s Nickname (Mamma Daddy, Motherfucker, Dude, Babe, Mummy, Bunny). The reason for slang used in Jessie J lyrics are to make them look unique and interesting, keep up with the times, add beauty to the tone in singing, and can make them shorter than grammatical words.